China's development co-operation - Schwarz, Rolf (OECD Publishing, 2023)
This paper traces the history of China's development co-operation system and looks into its practices, touching upon implementation gaps with established international norms and practices
Keywords: Environment; Development; Economics; Trade; China, People's Republic